2005
DOI: 10.1039/b406885h
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise pattern modification of neuronal network in photo-thermally-etched agarose architecture on multi-electrode array chip for individual-cell-based electrophysiological measurement

Abstract: We have developed a procedure for stepwise topographical control of network patterns and neurite connection directions between adjacent living neurons using an individual-cell-based on-chip multi-electrode array (MEA) cell cultivation system with an agarose microchamber (AMC) array. This procedure enables flexible and precise control of the cell positions and easy and flexible control of the pattern modification of connections between the cells in AMCs through stepwise photo-thermal etching in which a portion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
80
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 22 publications
1
80
0
1
Order By: Relevance
“…Jimbo et al (1993) first monitored the electrical activity of patterned neuronal networks with MEAs. More recently, Suzuki et al (2004Suzuki et al ( , 2005 demonstrated the possibility of specifically designing a neural architecture on MEA substrates; they were able to control the growth and connections of a hippocampal cell culture by using a laser to dynamical ablate an agarose layer to create channels and pits that entrap neurons and guide neuronal growth. Other examples in the literature are related to the patterning or confinement of neurons extracted from invertebrate (Fromherz, 2003;Claverol-Tinturé et al, 2005, in press).…”
Section: Introductionmentioning
confidence: 98%
“…Jimbo et al (1993) first monitored the electrical activity of patterned neuronal networks with MEAs. More recently, Suzuki et al (2004Suzuki et al ( , 2005 demonstrated the possibility of specifically designing a neural architecture on MEA substrates; they were able to control the growth and connections of a hippocampal cell culture by using a laser to dynamical ablate an agarose layer to create channels and pits that entrap neurons and guide neuronal growth. Other examples in the literature are related to the patterning or confinement of neurons extracted from invertebrate (Fromherz, 2003;Claverol-Tinturé et al, 2005, in press).…”
Section: Introductionmentioning
confidence: 98%
“…In contrast, as a 1480-nm IR laser has absorption to water, all the agar on the light pathway is heated and melted. The changed sol state agar is dispersed into the agar gel and holes or tunnels are formed in the agar layer applied even during cultivation, so we can change the network pattern of nerve cells during cultivation by adding microchannels between two adjacent microchambers in a step-by-step fashion Suzuki et al 2005). We used this new type of noncontact three-dimensional photothermal etching for the agar-microetching exploiting the characteristics of the two different infrared laser beam wavelengths (1480 and 1064 nm).…”
Section: Particle Separation Using Ultrasound and Electrostatic Forcementioning
confidence: 99%
“…Traditionally, two approaches have been used to control the locations of dissociated neurons on a certain region of the substrate, either employing containment such as micro-wells, micro-channels and micro-drops (Jimbo et al, 1993;Macis et al, 2007;Maher et al, 1999;Suzuki et al, 2005;Zeck and Fromherz, 2001), or adopting appropriate materials for surface patterning (Chang et al, 2003;Kleinfeld et al, 1988;Nam et al, 2004;Scholl et al, 2000). Indeed these approaches achieved a lot of successes, but it is still a challenge for precise manipulation of cells or treating the surface regions.…”
Section: Introductionmentioning
confidence: 99%